1984
DOI: 10.1002/app.1984.070291112
|View full text |Cite
|
Sign up to set email alerts
|

Pore structure analysis of purified, sodium hydroxide-treated and liquid ammonia-treated cotton celluloses

Abstract: SynopsisTo characterize the pore structures of purified cotton, NaOH-treated cotton, and liquid-NH,-treated cotton, we have (1) investigated the feasibility of preparing useful chromatographic columns from whole cotton fibers and (2) studied the elution behavior (penetration) of three selected classes of water-soluble solutes from columns of the three types of cotton fibers. The solutes were series of common oligomeric sugars, oxyethylene glycols, and oxyethylene glycol dimethyl ethers having molecular weights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…This molecule seems to have a somewhat larger elution volume than expected. The same phenomenon was also reported by Bredereck et al [ 23 ] and other authors [29] for different kinds of cellulosic materials. They suggested that an adsorption effect, probably owing to -OD/-OH exchange is present.…”
Section: Elution Curvessupporting
confidence: 89%
“…This molecule seems to have a somewhat larger elution volume than expected. The same phenomenon was also reported by Bredereck et al [ 23 ] and other authors [29] for different kinds of cellulosic materials. They suggested that an adsorption effect, probably owing to -OD/-OH exchange is present.…”
Section: Elution Curvessupporting
confidence: 89%
“…This treatment changes the crystallite structure from cellulose I to cellulose III. Water absorbency and dyeing properties with the treatment are almost unchanged, despite a considerable decrease in crystallinity [2][3][4][5][6][8][9][10][11].Although the decrease in crystallinity with the customary sodium hydroxide mercerization is smaller than that with the liquid ammonia treatment, dyeing properties increase considerably compared with the liquid ammonia, which greatly contributes to a soft hand [ 13]. Previously, we investigated the effect of liquid ammonia and sodium hydroxide/liquid ammonia treatments on mechanical properties with the KES instrument in relation to fabric hand [ 12].…”
mentioning
confidence: 99%
“…Mercerized fibers are more reactive to aqueous chemical reagents and are more accessible to dye molecules. Rowland et al (20) measured the increase in pore volume for natural and mercerized cotton, finding that mercerization increased the pore volume by 45-55%. They found less difference in the pore volume occupied by higher molecular weight molecules.…”
Section: Resultsmentioning
confidence: 98%